2011 15th International Conference on Advanced Robotics (ICAR) 2011
DOI: 10.1109/icar.2011.6088575
|View full text |Cite
|
Sign up to set email alerts
|

Foot bone kinematics at half and three quarters body weight: A robotic cadaveric simulation of stance phase

Abstract: Lower limb cadaveric robotic gait simulators have been employed to model foot bone kinematics during the stance phase of gait. Often the simulations are performed at reduced body weight (BW) but the effect of this limitation on foot bone kinematics has not been quantified. In this study we utilized the robotic gait simulator (RGS) to measure in vitro foot bone kinematics at different applied ground reaction forces (GRFs) (50% BW and 75% BW). The RGS simulated gait by replicating in vivo tibial kinematics, GRFs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…This will influence the measured outcome parameters during the simulations. However, reports in literature 54 have demonstrated that such scaling has negligible influence on the resulting bone kinematics. Third, cadaveric studies usually involve small number of subjects, hindering strong conclusions given the lack of extensive statistical testing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This will influence the measured outcome parameters during the simulations. However, reports in literature 54 have demonstrated that such scaling has negligible influence on the resulting bone kinematics. Third, cadaveric studies usually involve small number of subjects, hindering strong conclusions given the lack of extensive statistical testing.…”
Section: Discussionmentioning
confidence: 97%
“…The relative position of the bones was documented in a static position of the foot under varying loads of 0, 222, 445 and 667 N compression of the tibia against the sole of the foot. Many groups documented foot bone kinematics during dynamic simulations of gait, starting with Hamel et al 51 (documenting tibia, talus, calcaneus) followed by Nester et al 52,53 (documenting tibia, talus, calcaneus, navicular, cuneiforms, cuboid, metatarsals 1, 2, 3, 4 and 5); Whittaker et al, 26 Aubin et al 54 (documenting tibia, talus, calcaneus, navicular, medial cuneiform, cuboid, metatarsals 1, 3 and 5); Peeters et al, 24 Burg et al, 55 Okita et al 56 (documenting tibia, talus, calcaneus, navicular, cuboid).…”
Section: Research Questions Addressed Through In Vitro Experimentationmentioning
confidence: 99%
“…Finally, reduced forces (50% body weight) were applied on the tendons during the measurements, which is an inherent limitation of in vitro simulations. Some researchers performing in vitro simulations use reduced muscle forces to ensure cadaveric integrity [22,25], with a typical reduction of the muscle forces by 50%, with reported limited effect on bone kinematics [2].…”
Section: Discussionmentioning
confidence: 99%